Negotiating City Identity through Creative Economy - Aulia Suminar Ayu; Prihatin Dwihantoro; Ghozian Aulia Pradhana (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2021)
Creative economy is not only contributed toward social welfare but also creates identity. This case study takes place in Kendal Regency Central Java Province. The purposes of this study are to observe the creative economy landscape, to give initial data and conceptual input for the Kendal Regency Government to conceptualize their city branding. As exploratory research, this research is using mixed methods. Quantitative descriptive data was gathered by the survey on the creative economy subsectors. Qualitative data were taken from non-participant observation, semistructured interviews, and literature review. This exploratory study found that 10 of 16 creative economy subsectors have existed in Kendal Regency. They are visual communication design; product design; film, animation, video; photography; craft art; culinary; fashion; art performance; and music. These clusters can be used as city identity to formulate city branding, especially the craft art; culinary, film, animation, video; and art performance. Unfortunately, these potential resources were not involved on city branding created by the local government. In symbolic interactionism, people and their environment influence each other in culture-making processes. And so, in the processes of city branding. All the elements of the city should be in synergy to make a city branding. But it is not found in Kendal Regency. __________The original draft of this article has been presented at the 6th International Conference on Social and Political Sciences (ICoSaPS) 2020, Strengthening Resilient Society in The Disruptive Era, Surakarta, October 7-8th, 2020.